Auckland University of Technology (AUT), Faculty of Health and Environmental Sciences Research Roadshow 2024 - Conn, Cath; Sharma, Srishti; Foster, Mandie; Neufeld, Michael; Nayar, Shoba; Trafford, Julie; Sisodia, Renu; Charania, Nadia; Said, Ayan; Nikolai, Jennifer; Water, Tineke; Fernandez, Daniel; et al. (Child and Youth Health Research Centre, Auckland University of Technology, 2024)
AUT’s Faculty of Health and Environmental Sciences Research Roadshow is an annual event showcasing the diversity of research undertaken by faculty researchers, and postgraduate students. The 2024 faculty research roadshow was held on Thursday 12 September at AUT’s North Campus. The AUT Child and Youth Health Research Centre investigates the impact of illness and disability, home and family, health services, nutrition, physical activity and the wider environment on young people. We are committed to providing a space for young people’s voices. CYHRC presented members’ research abstracts.